Students’ Sensory referred on Learning Styles at English Education Department of Universitas Muhammadiyah Sorong - Ahmad Wael; Heriyanti Tahang; Hasanudin Hasanudin; Ira Siregar (Universitas Muhammadiyah Sorong, 2022)
This research aims to find out the students’ sensory preferred on learning style in learning English at English Department of Sorong Muhammadiyah University. Learning styles is a part of human being. Every person has an individual learning style. Individuals in learning has a variety of ways, some learned by listening, some learned by reading, and each students bring their own style to the classroom. Similarity, just as the learners learn in different ways, so also lecturer teach in different ways. This research was conducted in English Department of Universitas Muhammadiyah Sorong, the researcher took the representative of two classes at fifth semester. The researcher use questionnaire and Interview to find out the students’ sensory preferred learning style in learning English. The researchers found that the result of interview students dominant used visual learning style and 28.2% of participants is visual learners. However, visual learners were majority, the lecturer also discovered that students were able to receive the information when the lecturer delivered the information in auditory or kinesthetic way. The researchers found that language learning style between result interview and questionnaire were same. Visual learners are minority. In this case, the teacher needs to help students when they feel hard to understand. The teacher should also create the best appropriate teaching method to fulfill students’ language learning style during English class. Keyword: Student’s Preferred, Learning Styles, Learning